THE UPPER COMPLEMENT CONNECTED EDGE GEODETIC NUMBER OF A GRAPH (International Journal of Food and Nutritional Sciences, 2022)
A complement connected edge geodetic set of ???? is called a minimal complementconnected edge geodetic set of ???? if no proper subset of ???? is a complement connected edgegeodetic set of ????. The upper complement connected edge geodetic number ????????????????+ (????) is themaximum cardinality of a minimal complement connected edge geodetic set of ????. Some generalproperties satisfied by this concept are studied connected graphs of order p ≥ 3 with ????????????????+ (???? to be???? − 1 is given. It is shown that for every pair of integers ???? and ???? with3 ≤ ???? ≤ ????, there exists aconnected graph ???? with ????????????????(????) = ???? and ????????????????+ (????) = ????,where upper complement connected edgegeodetic number of a graph.